Atomistic simulations to study shock and ultrashort pulse response of high entropy alloy. (2022) - Kumar Singh, Sandeep; Chaurasia, Ankur; Parashar, Avinash
Abstract: This article aimed to study the shock compression and ultrashort pulse shock compression behavior of multi-elemental alloy, high entropy alloy (HEA), and single-crystal Ni. Non-equilibrium molecular dynamics (NEMD) based simulations were utilized in this article with the help of EAM potential to capture the deformation under dynamic and complex loading scenarios in HEA (Co-Cr-Cu-Fe-Ni) and single-crystal Ni. Simulations were performed with continuous shock compression and ultra-short shock pulse traversing the atomic configuration at velocity 0.75 km/s. Simulation helps capture the distribution of pressure and velocities in the simulation box as a function of the time from the onset of the shock front. Simulation helps capture the distribution of pressure and velocities in the simulation box as a function of the time from the beginning of the shock front. It was concluded from the MD simulations that the insertion of nano-voids in the path of the shock front helps in dispersing the energy and reducing the speed of the shock front. Nano-voids significantly affect the shock deformation of crystals and help in inducing plastic deformation in the HEA and Ni, even at shock velocities below Hugoniot elastic limit (HEL). Nucleation of dislocation from the nano-voids is more significant in HEA crystal as compared to Ni. The onset of plastic deformation in HEA and higher dislocation densities helps in dispersing the energy of the shock front, and the performance of HEA improved at higher shock velocities. The results in this article will help develop high entropy alloys for applications containing complex loading scenarios such as high strain rate loading experienced in space structures and armor vehicles.